The Expression and Clinical Significance of PCNAP1 in Hepatocellular Carcinoma Patients. (18th February 2022) - Chen, Yanhong; Zhang, Jiao; Liu, Jia; Wang, Jianguo; Shi, Chao; Lu, Lu; Cheng, Xing; Niu, Guoping; Zhang, Shuangshuang
Abstract : Background . Long noncoding RNAs (lncRNAs) play an important role in many cancer progression. The aim of this study was to evaluate the expression level and clinical significance of the lncRNA, proliferating cell nuclear antigen pseudogene 1 (PCNAP1), in cancer tissue and the plasma of patients with hepatocellular carcinoma (HCC). Methods . Quantitative real-time polymerase chain reaction was used to detect the expression of PCNAP1 in HCC tissue, adjacent tissue, and plasma. Spearman's rank correlation analysis was performed to assess relationships among cancer tissue, plasma PCNAP1, and plasma AFP. Kaplan–Meier analysis was used to assess survival of HCC patient with high and low expression of PCNAP1. The survival difference was compared by the log-rank test. The use of plasma levels PCNAP1 for diagnosing HCC was evaluated by receiver operating characteristic curve analysis. Results. The expression of PCNAP1 in HCC tissue was significantly higher than in adjacent tissue (P < 0.01 ). The PCNAP1 levels were related to the TNM stage, lymph node metastasis, and tumor maximum diameter (P < 0.05 ) but were not related to gender and age (P = 0.459 and 0.656). Patients with greater levels of PCNAP1 had poorer survival than patients with lower levels of expression (P < 0.01 ). Compared to the healthy control group, a gastric cancer group, and a colorectal cancer group, HCC patient plasma levels of PCNAP1 were significantly greater (P < 0.01 ). The area under the curve (AUC) of plasma PCNAP1 in HCC patients was 0.83 (95% CI: 0.78-0.88). With a cut-off value of plasma PCNAP1 at 1.27, an HCC diagnostic sensitivity of 70.08%, and a specificity of 85.04%, was the maximum diagnostic efficiency achieved. Conclusion. This study demonstrates PCNAP1 levels to be increased in HCC patients. As such, PCNAP1 may be a new tool useful in disease diagnosis and prognosis.